Musculoskeletal impairments and dysfunction in individuals with head and neck cancer following surgery with neck dissection—a systematic review - Mohamad, Norazlin; Oliveira-Souza, Ana Izabela Sobral de; Ntoukas, Stephanie M.; Castro-Carletti, Ester Moreira de; Munajat, Munayati; Dennett, Liz; Courneya, Kerry S.; Armijo-Olivo, Susan; McNeely, Margaret L. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Various forms of head and neck cancer (HNC) surgery that include a neck dissection procedure have been shown to negatively influence the neuromusculoskeletal function of the structures affected. This review aimed to identify the neuromusculoskeletal impairments experienced by individuals with HNC following surgery involving different types of neck dissection procedures. Methods: The search was conducted in four databases, encompassing randomized control trials (RCTs), cross-sectional studies, and cohort studies that explored neuromusculoskeletal impairments and dysfunction following HNC surgery. The risk of bias in the included studies was assessed using the ROB 2 tool for RCTs and the ROBINS-I tool for non-RCTs. Results: Sixty-seven studies were included (prospective cohort studies n = 29; cross-sectional studies n = 21; retrospective studies n = 13; and RCTs n = 4). This review revealed diverse neuromusculoskeletal impairments and disabilities in individuals with HNC after undergoing various types of neck dissection. The overall quality of evidence was low due to methodological limitations and variability in assessment tools. Conclusions: The extent and type of neuromusculoskeletal impairment resulting from surgery varied depending on the type of surgery and the outcome measures used. Further high-quality studies with standardized assessment, consistent outcome measures, and long-term follow-up are needed to improve the credibility of research in this area